THE ROLE OF ENGLISH LANGUAGE SKILLS FOR WAITERS IN IMPROVING SERVICE QUALITY AT COMPASS ROSE RESTAURANT THE ANMON RESORT BINTAN - Williandani, Mega; Lumban Gaol, Rikki Nelson (Jurnal Ilmiah Akomodasi Agung, 2025)
This research examines the role of English language skills among waiters in enhancing service quality at the Compass Rose Restaurant of The ANMON Resort Bintan. As an international language, English plays a vital role in the hospitality industry, especially in interactions between waiters and foreign guests. This study aims to analyze the English proficiency levels of waiters, identify its impact on service quality, and propose recommendations for service improvement. The research employs a qualitative approach through direct observation and in-depth interviews. Informants include one food and beverage manager, one supervisor, ten waiters, and six restaurant guests, selected to provide comprehensive data. Findings reveal that the English-speaking skills of waiters are still suboptimal, particularly in speaking, leading to miscommunications during food and beverage orders. These misunderstandings often result in incorrect orders and guest complaints, which significantly affect guest satisfaction and overall service quality. The study recommends a consistent and structured English language training program under the supervision of the food and beverage manager. The program should focus on practical communication skills relevant to restaurant service tasks. Implementation of this recommendation is expected to improve service quality and create a more satisfying dining experience for guests at Compass Rose Restaurant.